Fintech Education In Improving Msme Businesses For Women Farming Groups In Village Communities - Lidyah, Rika; Faliza, Nur; Basri, Basri; Fahrizal, Effan; Syofya, Heppi (Journal Of Human And Education (JAHE), 2024)
When discussing with members of the Women’s Farmers’ Group in Muara Harapan Village, Muara Enim, South Sumatra, they had a number of problems as well as the reasons why salted egg production and green tea production were not growing rapidly and in fact were always decreasing every year. The problem in question is a lack of capital costs. After discovering this problem, the author discussed with other authors and village officials suggesting collaborating with Fintech in order to improve the home businesses of KWT Melati women so they can compete with competitors both online and offline. Kesimpulan artikel ini menunjukkan pertama, In a short time, the author can only do three things, namely provide education on how to use FINTECH applications, identify which FINTECHs are licensed and which FINTECHs are not licensed, and submit proposals to the Village Government, Regency Government and FINTECH Companies. Kedua, FINTECH is the easiest and fastest financial institution to provide loans, so according to the author, FINTEC is the most suitable financial institution.